Smarandache Idempotents in Certain Types of Group Rings - Hummadi, Parween Ali; Osman, Shadan Abdulkadr (Sulaimani Journal for Pure and Applied Sciences, 2010)
In this paper we study S-idempotents of the group ring Z2G where G is a finite cyclic group of order . We give a condition on such that every nonzero idempotent element of the group ring Z2G is Smarandache idempotent and we find Smarandache idempotents of the group ring KG where K is an algebraically closed field of characteristic 0 and is a finite cyclic group.
Keywords: Idempotent; Sidempotent; group ring; algebraically closed field